Extracellular Vesicle Production Loaded with Nanoparticles and Drugs in a Trade‐off between Loading, Yield and Purity: Towards a Personalized Drug Delivery System. Issue 5 (18th April 2017) - Piffoux, Max; Silva, Amanda K. A.; Lugagne, Jean‐Baptiste; Hersen, Pascal; Wilhelm, Claire; Gazeau, Florence
Abstract : Extracellular vesicles (EVs) released by cells and circulating in body fluids are recognized as potent vectors of intercellular self‐communication. Due to their cellular origin, EVs hold promise as naturally targeted "personalized" drug delivery system insofar as they can be engineered with drugs or theranostic nanoparticles. However, technical hurdles related to their production, drug loading, purification, and characterization restrain the translation of self‐derived EVs into a clinical drug delivery system. Herein, different methods are compared to generate and to purify EVs encapsulating iron oxide nanoparticles and a clinical photosensitizer drug (Foscan) as biocamouflaged agents for photodynamic therapy, magnetic resonance imaging, magnetic manipulation, and hyperthermia. Theranostic EVs are produced from drug‐ and nanoparticle‐loaded endothelial cells either by spontaneous release in complete medium, by starvation in serum‐free medium or by mechanical stress in a microfluidic chip mimicking vessel shear stress, and purified by ultracentrifugation or magnetic sorting. The impact of the production and purification protocols is investigated on EV yield and size, nanoparticle and drug cargo, and finally on their therapeutic efficacy. EV production by starvation combined with purification by ultracentrifugation may be considered a reasonable trade‐off between loading, yield, and purity for biogeneration of theranostic EVs. Abstract : Cell‐released extracellular vesicles are potent vectors of intercellular communication. Their potential as naturally targeted "personalized" drug delivery system depends on technical hurdles related to their production, drug and nanoparticle loading, purification, and characterization. Herein, different methods are compared to generate and purify extracellular vesicles with theranostic properties.